RICARDIAN EQUIVALENCE IN INDONESIA - Adji Pratikto Pratikto; Indira Kirana; YB Suhartoko (Jurnal Ekonomi Trisakti, 2022)
Expansionary Fiscal Policy in the form of Deficit Fiscal is still being debated due to differences in views regarding the effect of budget deficits. The Ricardian Equivalence disciple argues that Deficit Fiscal Policy has a neutral impact on consumption. In contrast, Non-Ricardians (Keynesian and Neoclassical) argue that Budget Deficit Policy affects Private Consumption. Government policies affect private consumption through deficit fiscal policies such as budget deficits, government spending, taxes, and government debt. This study analyzes the effect of the fiscal deficit on consumption and observes the existence of the Ricardian Equivalence View in Indonesia. The estimation model used is the Vector Error Correction Model (VECM) through IRF and VD testing with time series data from 1980-2018. The results showed that the Budget Deficit Policy had a significant positive effect on private consumption, where the Fiscal Deficit shock was responded positively by Private Consumption. So that the Ricardian view does not apply in Indonesia and is more inclined to the Keynesian view. The positive response continues in the long term permanently, where 58.42% of the variation in the formation of the Private Consumption indicator (in period 10), is a Budget Deficit.